Hospital Hallucinosis - where to look for the cause of the delirious syndrome in a geriatric patient and what management to implement - Karolina Tomczyk; Karolina Jurasz; Natalia Chojnacka; Jakub Klarycki; Dominika Podgórska; Radosław Cymer; Ewa Rzeska; Miłosz Sanecki (Kazimierz Wielki University, 2024)
Delirium syndrome is a serious, and often underestimated, problem arising in elderly patients. The number of accurate diagnoses of this acute condition is significantly lower than actuall present. This is often due to the attribution of its symptoms to the underlying disease. Delirium syndrome, by leading to perceptual disturbances in the patient, impairs his functioning and threatens health and even life of a patient. The pathophysiology of the onset of delirium is not well understood, with many factors influencing its development. Those directly related to the patient (predisposing), as well as triggering factors. In geriatric patients, the risk of developing delirium is much higher than in younger patients due to the depletion of the body's functional reserves. Homeostasis of the body's systems is disturbed even with small negative stimuli. It is important to closely observe the patient, taking a well-gathered history of the patient's baseline health status and the changes that have occurred in the patient's condition. A well-conducted physical examination and diagnostic imaging is essential. There is no universal scheme for managing a patient who is delirious. It is important to take an personalized approach and quickly find the cause and try to treat it. We can use commonly available scales and guidelines for diagnosing the delirious syndrome, such as ICD-10, DSM-5 or CAM, to make the accurate diagnosis easier. It has been shown that with the help of non-pharmacological preventive management, we can significantly reduce the number of consciousness disorders that appear in elderly patients under the course of delirium. In severe cases, pharmacotherapy comes to our aid.